Shadow scale - Hartman, Rachel 1972- (New York Random House, 2015)
Seraphina, half-dragon and half-human, searches for others like her who can make the difference in the war between dragons and humans in the kingdom of Goredd--Provided by publisher.
Sequel to: Seraphina.
Keywords: War -- Fiction; Dragons -- Fiction; Courts and courtiers -- Fiction